Haematological and Histopathological Effects of Mosquito Coil Smoke on Kidney-An Experimental study on Albino Rat. - Masooma Syed; Sheikh Tousia; Kamaldeep Singh Balowria; Nusrat Jabeen; Nafis Ahmad Faruqi; Arshi Beg (Academia Anatomica International, 2019)
Introduction: Mosquitoes have long been identified as the main vectors of many human and animal diseases like West Nile fever, malaria, dengue, etc. Mosquito coils are the most preferred mosquito repellent products used especially in low-income communities, due to cheap price. The most common active ingredients in mosquito coils pyrethroids, are known to cause nephrotoxicity and,haematoxicity. However substantial data is lacking on the effects of mosquito coils containing d-trans allethrin. Subjects and Methods: In this study we report the histological and haematological effects of  smoke from  such coil on albino rat (Wistar). The study was performed on Thirty albino rats divided into five groups (A, B, C, D, E) of six animals each. Control group A we left unexposed to coil smoke while rest (B-E) were exposed for 4, 6,8,10 weeks respectively. Results: We observed a statistically significant increase in the levels of serum  urea and creatinine  in experimental groups C, D and E. Levels of serum sodium and potassium remained unaffected in the experimental animals. Histopathological studies on kidneys revealed generalised degenerative changes proportional to quantity of coil smoke exposure. Conclusion: General human masses should be made aware about such possible hazards and adequate measures should be taken to ensure minimal exposure to coil smoke during domestic use.